Dynamics and Transformations in Small Disciplinary Communities: Some Remarks on Institutional and Paradigm Shifts in Ethnology/Anthropology in Post-Yugoslav States - Radović, Srđan (Bulletin of the Institute of Ethnography SASA, 2022)
The paper presents an overview of some major paradigmatic and thematic currents developing in ethnology (or ethnologies) in what used to be Yugoslavia and after the breakup of this country; these processes are discussed also by monitoring the evolution of institutions and through dynamics in numerously small disciplinary communities of ethnologists/anthropologists. After almost a hundred years of relatively slow paradigmatic, yet intensive institutional development, ethnological communities in this part of Europe accelerated their uplift in the last quarter of the 20th century with their theoretical modernization (sometimes also coined ‘anthropologization’), which is in the most recent times followed by acceleration in overall scholarly production (bordering on proliferation), of research topics and outputs (which can also be dubbed as ‘projectification’), much in line with trends enveloping in the global scientific markets. The paper calls upon a renewed collaboration between academic and museological anthropology as a potential impetus for increasing the discipline’s local relevance and for the creation of new research areas.
Keywords: history of ethnology; (cultural) anthropology; former Yugoslavia; ‘anthropologization’; ‘projectification’; small disciplinary communities